2023
DOI: 10.3389/fonc.2023.1182748
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes of immunotherapy with or without chemotherapy in first-line treatment of advanced non-small cell lung cancer

Veronika Pelicon,
Tanja Cufer,
Lea Knez

Abstract: BackgroundImmunotherapy alone (mono-IT) or combined with chemotherapy (chemo-IT) has recently become the cornerstone of first-line treatment for advanced non-small cell lung cancer (NSCLC) patients. Here, real-world outcomes of first-line mono-IT and chemo-IT of advanced NSCLC treated within routine clinical practice at a single academic center in the Central Eastern European (CEE) region are presented.Materials and methodsA total of 176 consecutive patients with advanced NSCLC treated with mono-IT (118 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In many real-world studies, [20][21][22][23][24] outcomes comparable to RCTs have been observed, despite including patients with poor prognostic factors such as high tumor burden, unstable or untreated CNS metastasis, and ECOS-PS greater than 2 19 who are typically excluded from RCTs. In immunotherapy-based group, 15% of patients had ECOG-PS greater than 2, and 24% had CNS metastasis at baseline.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In many real-world studies, [20][21][22][23][24] outcomes comparable to RCTs have been observed, despite including patients with poor prognostic factors such as high tumor burden, unstable or untreated CNS metastasis, and ECOS-PS greater than 2 19 who are typically excluded from RCTs. In immunotherapy-based group, 15% of patients had ECOG-PS greater than 2, and 24% had CNS metastasis at baseline.…”
Section: Variablesmentioning
confidence: 99%
“…Caucasian patients, 63% have PD-L1 positive tumors, 33% of Chinese patients exhibit PD-L1 positivity, smoking is a share risk factor that increases likelihood of PD-L1 high expression. 16,17 Hence, researchers recognize the significance of realworld data [18][19][20][21][22][23][24] in elucidating the efficacy of immunotherapy. In Asian countries such as China, Japan, and Korea, there are real-world data [25][26][27][28][29] comprising 1390 treated patients with immunotherapy, either with or without chemotherapy demonstrate survival benefits consistent with clinical studies.…”
Section: Introductionmentioning
confidence: 99%